Soul in Vedanta Metaphysics and Emersonian Philosophy - Chalise, Keshav Raj (JODEM: Journal of Language and Literature, 2022)
Vedanta philosophy, as the foundation of Hindu philosophy, has talked much about the existence and role of Atma in life in depth, and Atma’s relationship to Paramatma as the unity of the worldly living beings and the absolute, Brahma. This notion deals with the idea that Atma is immortal and unchanged, but it undergoes transformation from body to body. The western Christian philosophy also has the notion of Atma with the name "the soul," but Christian philosophy gives the message of the changeability of the soul. Being brought up in Christian culture and tradition, Emerson focuses on the soul's spirituality in his writings and develops the theory of transcendentalism, but as influenced by Vedantic philosophy, his concept of the soul departs from pure Christian tradition and gets linked with the Vedantic concept of Atma and Paramatma. This study examines how Vedanta metaphysics and Emersonian transcendentalism share common ground in the perception of Atma and Paramatma, and finds the connection between Vedantic metaphysical notion of the soul as Atma and Paramatma and American transcendental view of the soul and the Over-soul proposed in Emerson’s writings. This study is significant to make a meaningful connection between the Eastern Vedic viewpoints with the Western viewpoints in the mode of philosophical understanding.